2003
DOI: 10.1002/ejic.200200638
|View full text |Cite
|
Sign up to set email alerts
|

Mono‐Dithiolene Molybdenum(IV) Complexes of cis‐1,2‐Dicyano‐1,2‐ethylenedithiolate (mnt2−): New Models for Molybdenum Enzymes

Abstract: New mono‐dithiolene molybdenum(IV) complexes of cis‐1,2‐dicyano‐1,2‐ethylenedithiolato [(mnt)2−] have been synthesized as models for molybdenum enzymes, with 4,4′‐di‐tert‐butyl‐2,2′‐bipyridine (Bu2bpy) and, N,N′‐tetraethylethylenediamine (Et4en) as ancillary ligands, and characterized by IR, UV/Vis, elemental analysis, ESI‐mass and electrochemical techniques. The temperature‐dependent 1H NMR spectra, recorded in CD3CN solution, indicated that [MoO(mnt)(Bu2bpy)] (1) has a rigid structure but [MoO(mnt)(Et4en)] (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…These show Mo(V) rhombic EPR signal and can be electrochemically reduced to Mo(IV), though the reduced complexes were not isolated. Some nondithiolene oxo–Mo(V) complexes were reported with a view to understand the EPR signature of SO. Coordination of three sulfur atoms in the equatorial plane (two of which are from dithiolene) is the essential qualification for a compound to be considered as a structural analogue of reduced sulfite oxidase. No synthetic complex mimicking the fully reduced state of sulfite oxidase has been synthesized with dithiolene and thiolato ligation to date.…”
Section: Introductionmentioning
confidence: 99%
“…These show Mo(V) rhombic EPR signal and can be electrochemically reduced to Mo(IV), though the reduced complexes were not isolated. Some nondithiolene oxo–Mo(V) complexes were reported with a view to understand the EPR signature of SO. Coordination of three sulfur atoms in the equatorial plane (two of which are from dithiolene) is the essential qualification for a compound to be considered as a structural analogue of reduced sulfite oxidase. No synthetic complex mimicking the fully reduced state of sulfite oxidase has been synthesized with dithiolene and thiolato ligation to date.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, significantly fewer are a type of mono(dithiolene)MoS complex, resulting in only one series of [Tp*Mo V/IV S(dithiolene)] 0/− complexes (Tp* = hydrotris(3,5-dimethylpyrazol-1-yl)borate); , this indicates that the incorporation of one terminal sulfido group into a mono(dithiolene)Mo center is a still difficult task. With respect to mono(dithiolene)MoO complexes, some types of the species have been synthesized with mono-, di-, or tridentate coligands. Therefore, development of new synthetic procedures for various types of mono(dithiolene)MoS/O complexes is necessary to expand the fields of bioinorganic chemistry as well as material science.…”
Section: Introductionmentioning
confidence: 99%
“…In order to verify whether the slowness of the OAT reaction was indeed due to dimer formation, a solution of 3 mM complex 5 in the presence of oxidizing agent trimethylaminoxid (TMAO) in acetonitrile was prepared and monitored by UV-Vis spectroscopy under anaerobic condition. It was observed that after the initial formation of the transient Mo VI O 2 species (here very broad signal at λ max : 540 nm), it swiftly decomposed again while the signal for the catalytically inert Mo2VO 3 species (typical signal at λ max : 375 nm) (Villata et al, 2000; Sugimoto et al, 2003; Pal et al, 2007) exhibited a steady rise (see Figure S22). The change in the UV-vis with the progress of the reaction exhibits clean isosbestic points indicating the simultaneous presence of only two (not three) species.…”
Section: Results and Discusionmentioning
confidence: 99%